Energy Harvesting Techniques for Wireless Sensor Networks: A Systematic Literature Review - Bernardo Yaser León Ávila (Energy Strategy Reviews, 2025)
Energy harvesting has emerged as a promising avenue for addressing the constraints imposed by battery lifespan in wireless sensor networks (WSNs), paving the way for more sustainable and autonomous operations. This paper presents a comprehensive and systematic literature review (SLR) that critically examines the latest advancements and methodologies in energy harvesting for wireless sensor networks (WSNs). The review encompasses the entire system architecture, including energy storage and power management systems. The review is based on bibliometric analysis and a detailed examination of an extensive collection of 196 peer-reviewed studies published between 2014 and 2023. The text provides a comprehensive assessment of diverse technologies, techniques, and mechanisms for extracting energy from environmental sources, including thermal, light, mechanical, radio frequency, chemical, and biological, to power a wireless sensor node device. Furthermore, the concepts of transducers, energy sources, and energy types are elucidated and defined, thus establishing a lucid framework for classifying and analyzing these techniques and technologies. Additionally, key trends, challenges, and future research directions are identified, emphasizing areas that require further exploration to advance the field, particularly in battery-less systems employing capacitors and supercapacitors.